Executive compensation and informed trading in acquiring firms around merger announcements - Ordu, Umut; Schweizer, Denis (Journal of Banking & Finance, 2015)
This paper analyzes informed trading in acquiring firms through (stock) merger announcements. We show that pre-announcement abnormal option volumes in acquiring firms strongly increase ahead of a stock merger (by approximately 300%). Furthermore, we show that the direction of option trades (puts or calls) prior to an announcement can predict post-announcement stock returns. Our results also indicate that higher wealth-to-performance sensitivities of top executives are related to higher abnormal put than call option trading before stock merger announcements. Overall, our results support the view that top executives have a hedging motive. They tend to purchase protection against, e.g., confounding (negative) information policies and/or empire-building mergers with negative NPVs, in order to avoid short-term salary losses (lower bonuses, lower stock options, etc.).